Human Computer Interaction (HCI) in Malaysia education / Saiful Amrie Basirun - Basirun, Saiful Amrie (2009)
This project is about a study of Human Computer Interaction (HCI) education in Malaysia. It is focused on IPTA undergraduate program which offer HCI course. The main objective is to determine the importance of knowledge of HCI for undergraduate students and in the same time it can identify the programs that offered HCI course and the other HCI related course which is similar to the HCI course. This research used literature material as a guidance to archive the objectives. The data of this study is gathered from IPTA's website and to be confirm by interview and then the data been analyze to answer the research questions archive the objective.